Implementing Minority Language Preservation Policy in Urban Governance: A Collaborative Framework Analysis of Betawi Language Policy in Jakarta - Nana Yuliana; Tadjuddin Nur; Somadi Sosrohadi; Fathu Rahman (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: This study examines the implementation of Betawi language preservation policy in an urban context, focusing on policy design, implementation capacity, and collaborative governance. Objective: This study aims to identify factors limiting effective Betawi language revitalization in urban communities. Methods: A qualitative case study was conducted using policy document analysis, in-depth interviews, and field observations. Data were analyzed using George C. Edwards III’s policy implementation framework and Ansell and Gash’s collaborative governance model. Results: Despite strong normative legitimacy, the policy has not achieved functional language revitalization. Weak translation of regulations into operational programs, limited human resources and learning instruments, and fragmented cross-actor coordination have produced symbolic outputs without transforming everyday language use. The study introduces the concept of symbolic-performative policy, describing policies that generate cultural legitimacy through institutionalized ceremonial activities but fail to internalize language functions in urban communities. Education remains the primary implementation arena but is not yet integrated into a sustainable language-use ecosystem. Conclusion: The policy’s limited effectiveness stems from disconnections among policy design, implementation capacity, and collaborative governance. Urban regional-language revitalization therefore requires an integrated, cross-sectoral language-use ecosystem beyond regulatory and ceremonial approaches.